MICA, a gene contributing strong susceptibility to ankylosing spondylitis. Issue 8 (1st June 2013) - Zhou, Xiaodong; Wang, Jiucun; Zou, Hejian; Ward, Michael M; Weisman, Michael H; Espitia, Maribel G; Xiao, Xiangjun; Petersdorf, Effie; Mignot, Emmanuel; Martin, Javier; Gensler, Lianne S; Scheet, Paul; et al.
Abstract : Objective: The human major histocompatibility complex class I chain-related gene A ( MICA ) controls the immune process by balancing activities of natural killer cells, γδ T cells and αβ CD8 T cells, and immunosuppressive CD4 T cells. MICA is located near HLA-B on chromosome 6. Recent genomewide association studies indicate that genes most strongly linked to ankylosing spondylitis (AS) susceptibility come from the region containing HLA-B and MICA . While HLA-B27 is a well-known risk genetic marker for AS, the potential effect of linkage disequilibrium (LD) shields any associations of genes around HLA-B with AS. The aim of this study was to investigate a novel independent genetic association of MICA to AS. Methods: We examined 1543 AS patients and 1539 controls from two ethnic populations by sequencing MICA and genotyping HLA-B alleles. Initially, 1070 AS patients and 1003 controls of European ancestry were used as a discovery cohort, followed by a confirmation cohort of 473 Han Chinese AS patients and 536 controls. We performed a stratified analysis based on HLA-B27 carrier status. We also conducted logistic regression with a formal interaction term. Results: Sequencing of MICA identified that MICA *007:01 is a significant risk allele for AS in both Caucasian and Han Chinese populations, and that MICA *019 is a major risk allele in Chinese AS patients. Conditional analysis of MICA alleles on HLA-B27 that unshielded LD effect confirmed associations of the MICA alleles with AS. Conclusions: Parallel with HLA-B27, MICA confers strong susceptibility to AS in US white and Han Chinese populations.